Strategi Lembaga Bantuan Hukum dalam Menangani Perkara Perdata di LKBHI IAIN Salatiga - Jamaludin, Nurrun (Al-Istinbath: Jurnal Hukum Islam, 2019)
This research try to find out the strategy of handling case civil case at the Islamic Legal Consultation and Assistance Institute of IAIN Salatiga, nowadays many Legal Aid Institute just focus on litigation process to get money from the Ministry of Justice and Human Rights, but the main function of Legal aid Institute are neglected such as legal studies and legal counseling, besides forgetting the legal function as the aspire of the law, that is to be social control and civil engineer. This research/study using evaluative analysis method, the method is collecting and presenting all LKBHI data since 2016-2018 then analyze the actual facts and then analyze them rationally based on juridical principles through library research and on the spot research.The finding of this research indicate that LKBHI IAIN Salatiga has finished many civil case, but many solution using non litigation process, when the strategy built to resolve cases using a psychological approach to the parties, while also applying procedures to the team to resolve client’s case with negotiation and mediation, where all participants on the team is active and doing the work based on their own expertise. Then the results lead by LKBHI IAIN Salatiga the solution is a win-win solution are quite significant.